Geometric Design for Light Trapping in Bifacial Thin-Film Photovoltaics - Kim, Jae-Hyun; Park, Geon-Tae; Kang, Rira; Ju, So-Yeon; Yu, Semin; Lee, Byunghong; Kim, Sun-Kyung (IEEE journal of selected topics in quantum electronics, 2025)
Modern photovoltaics (PVs) are increasingly designed to be thinner and more transparent, thus enabling seamless integration into buildings and vehicles in urban environments. However, semitransparent thin-film PVs face inherent challenges in sunlight capture due to the limited volume of absorbing materials and the absence of efficient light-trapping strategies. Herein, we report a geometric design for light trapping in thin-film PVs using a wedge-shaped microprism sheet. This microprism sheet, attached to the planar surface of thin-film PVs, mitigates reflection losses at both external (air-cover) and internal (cover-PV cell) boundaries by leveraging light trapping. The light-trapping effect is quantitatively validated through angle-resolved transmittance measurements. The microprism sheet achieves near-unity external transmittance at all incident angles and redirects 81% of the internally reflected light back to the PV cell over typical solar incidence angles. Outdoor experiments conducted with semitransparent thin-film perovskite (PVSK) PVs demonstrate energy generation enhancements of >17% during daytime in vertically oriented bifacial configurations. These improvements are ascribed to the effective capture of direct sunlight on both the front and rear surfaces of the PVSK PVs. The geometric design of microprism sheets is facile yet effective for broadband light manipulation, offering a versatile solution for advancing solar energy devices and radiative coolers.